Podor na Mangartu - Hrvatin, Mauro (Geografski obzornik, 1995)
At the beginning of November some newspapers had reported that a rock fall occurred on the mountain Mangart in the western part of the Julian Alps, NW Slovenia. According to these reports we were seriously afraid that the fourth highest mountain of Slovenia would be soon reduced to scree and dust. After a field overview it turned out, that the journalists reports was exaggerate. The Mangart rock fall is just the result of usual geomorphological activity in the mountain environment
Keywords: geomorfologija; Mangart; naravne nesreče; podori; Slovenija